When social media meets low-cost airlines: Will customer engagement increase customer loyalty?. (March 2023) - Chou, Shihyu; Chen, Chi-Wen; Wong, Minnie
Abstract: During the last few decades, there has been an increased use of social media by low-cost airlines (LCAs) to interact with their customers and generate customer engagement. Customer engagement developed by social media might mitigate the negative impact of the low-pricing strategy adopted by LCAs on trust and commitment. However, research in this area is still rare. To fill this research gap, this study examines whether LCAs can still earn customers' trust and relationship commitment in the low-pricing market by using social media to develop customers engagement, which in turn leads to customer loyalty toward LCAs. Drawing on the trust-commitment theory, this study establishes a research model to examine the impact of customer engagement on trust, commitment, and customer value creation, all of which influence customer loyalty. A total of 240 valid online questionnaires completed by subjects who were members of LCAs' social media pages in Taiwan were collected to conduct the statistical analysis for the research model by using the partial least squares structural equation modeling (PLS-SEM) technique. The results suggest that customer engagement in the LCA's social media page significantly affects trust, commitment, and customer value creation. Furthermore, trust and commitment mediate the relationship between customer engagement and customer loyalty. Implications for theory, practice, and future research directions are discussed.